KONTEN FOTOGRAFI JURNALISTIK YANG MENJADI VIRAL DI INTERNET - Ellen Agustine Saputra (Institut Seni Indonesia Yogyakarta, 2017)
With the presence of the Internet, journalistic photography can provide an opportunity to be more noticed by various societies. Social media and other online media accessed by billions of people each day therefore the spread of journalistic photography are wider. In this case the role of photojournalists becomes more crucial, Rothman (2012) explains that the beginning of motivational photojournalist plunge in the world of journalism due to the insistence in their hearts to announce something that is so important therefore they want to make a change. In this research will be discussed some journalistic photography that raised certain themes using content and structure of journalistic photography with significant results, then become viral on the internet. Some journalistic photography can be viral and some are not. The focus of this research is to find out the reasons and similarities in some journalistic photography that became viral on the Internet. This research uses qualitative content analysis method. Samples were selected based on the virality factor, 4 journalistic photography were taken from various sources and photographed by photographer with different background too. The first photo has been mentioned for 1,890,000 times; the second photo has been mentioned for 32,900,000 times; the third has been accessed for 22,600,000 times and the last has been accessed for 25,270,000,000 times. All four will be discussed based on the theory of journalistic photography, associated with the theory of virality.